حجّية الاستحسان عند الحنفيّة والشّافعيّة وآثاره في الحكم الشّرعيّ (دراسة مقارنة): Authenticity of Approval According to the Hanafis and Shafi’is and Its Effect on the Sharia Rules - Rahmat Rahmat; Sirajuddin Sirajuddin; Ahmad Syaripudin; Danang Danang (البصيرة: مجلة الدراسات الإسلامية, 2022)
The study aimed to know the sayings of the Hanafi and Shafi’i scholars regarding the authority of istihsan in inference and its effects on the legal ruling. The scientific method that the researcher followed to reach the most important results of the research is the descriptive method, the inductive method, and then the deductive method. The most important results from this research: The approval that the Hanafis adhere to is the following of the best of the two evidence, either a hidden analogy in contrast to a clear analogy, or the exception of a partial issue from a general origin or a universal rule that requires that. As for the Shafi’is, they considered istihsan to be a statement of desire and desire. And when the term istihsan settled on a specific idiomatic meaning, Imam Al-Shafi’i took a positive position on it, rather he mentioned issues whose legal ruling was deduced through him and declared that he said, whether it is recommended or desirable. Here it became clear that the disagreement is a verbal dispute. And that the work with the correct approval agreed upon shows the flexibility of the tolerant Sharia and to achieve the interests of the nation and to preserve the hardship from the methods of analogy.